Urea Super Granule: A Good Source of Nitrogen on Growth Yield and Profitability of Cabbage in Sylhet - Sarker, MMR; Shaheb, MR; Nazrul, MI (Journal of Environmental Science and Natural Resources, 2012)
An experiment was conducted in Sylhet under AEZ-20 (Eastern Surma-Kushiyara Floodplain) during 2007-08 and 2008-09 to find out the effect of Urea Super Granule (USG) on cabbage. There were five treatments viz. T1: recommended nitrogen (N) dose as prilled urea (PU), T2: recommended N dose as USG, T3: 10% less than recommended dose of N as USG, T4: 20% less than recommended dose of N as USG, and T5: farmers practice (average of 20 farmers N dose used as PU) used in the experiment. Results revealed that yield of cabbage increased significantly due to application of USG over PU. The highest head yield of cabbage 92.04 and 91.36 t ha-1 were obtained from the USG (recommended dose) in 2007-08 and 2008-09, respectively which was statistically similar with USG 10% less than recommended dose (84.78 t ha-1) instead of traditional PU. The treatments T3 and T4 were found more effective over PU, and N loss was also minimum than that of prilled urea where 10-20% N fertilizer could be saved by using USG instead of traditional PU. Regarding economic analysis, the higher returns were also obtained from the treatment T2 which was more profitable in terms of higher gross returns as well as Benefit Cost Ratio (BCR). DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11595 J. Environ. Sci. & Natural Resources, 5(1): 295-299, 2012